Optimasi Konten Pemasaran dan Platform Online dengan Teknik Search Engine Optimization - Mahadir Muhamad Erfin; Rifqi Mufiddin; Syahiduz Zaman (Maranatha University Press, 2022)
Running a business just doing production is not enough but must do optimal product marketing. Business actors who market their products through conventional marketing will be unable to compete with other entrepreneurs who market their products through online platforms because online platforms are now widely found via the internet. Conventional product marketing is done because they do not understand the right optimization techniques in product marketing, especially in marketing content optimization strategies and the use of online platforms. Optimization of content marketing and online platforms requires a technique known as SEO or Search Engine Optimization. This technique is used to help optimize marketing precisely in determining content and showing product content in internet searches through online platforms. Product content and optimized online platforms will provide a great help in product marketing. This study aims to explain marketing content optimization strategies and online platform settings so that they can display shrimp cracker product content posts on the search page. The results of this study are able to optimize the marketing content of the right shrimp cracker products and display product keyword search results on internet search pages through the online platforms Tumblr, TribunJualBeli, and Carousell.